(untitled) (International Journal of Engineering and Computer Science, 2017)
A wireless sensor network (WSN‟s) can be separated into multiple connected components due to the failure of some of its nodes, which is called a “cut.” In this paper, here the considered problem of detecting cuts by the remaining nodes of a wireless sensor network. By the proposal an algorithm that allows 1) Each and every node to detect when the connectivity to a specially designated node has been lost. 2) One or more nodes (that are connected to the special node after the cut) to detect the occurrence of the cut. The algorithm is distributed and asynchronous: Every node needs to communicate with only nodes which are within its communication range. The algorithm is based on the iterative computation of a fictitious “Electrical Potential” of the nodes. The convergence rate of the underlying iterative scheme is independent of the size and structure of the network. We demonstrate the effectiveness of the proposed algorithm through simulations and a real hardware implementation